The Gas Supply of Boston - Gray, John H. (Quarterly Journal of Economics, 1898)
The Gas Supply of Boston John H. Gray John H. Gray Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 12, Issue 4, July 1898, Pages 419–446, https://doi.org/10.2307/1882954 Published: 01 July 1898